Hubungan Kepatuhan Penggunaan Obat Inhaler (B2-Agonis + Kortikosteroid Inhalasi) dengan Kualitas Hidup Pasien Asma di RSUD Dr. Suhatman Mars Dumai dinilai Dengan Mars-5 dan M-aqlq - Octariany; Dewi Murni Manihuruk; Mhd. Wahyudi Azmi (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Asthma is a heterogeneous disease usually characterized by chronic airway inflammation. The disease is defined by a history of respiratory symptoms such as wheezing, shortness of breath, chest tightness, and coughing, which vary over time and intensity, as well as different expiratory airflow limitations. Asthma treatment can be classified as controllers or relievers where the goal of asthma treatment is to improve and maintain the quality of life of asthma patients so that they can live a normal life and perform their daily activities without hindrance. Asthma treatment should consider both the giver and receiver of the medication, including patient compliance. Patient adherence to medication is an important component of asthma treatment. Thus, improving adherence greatly impacts lung function improvement, while non-adherence will reduce quality of life and increase treatment costs. Asthma patients' quality of life can suffer if they are not adherent to their medication, which can limit their daily activities, such as exercising, not going to school, and missing work days. The disease can also cause physical, emotional, and social limitations that impact the patient's education and career. This study aimed to determine the relationship between compliance with the use of inhaler drugs (β2- agonists + Inhaled Corticosteroids) to the quality of life of asthmatics at RSUD dr. Suhatman MARS. This study was a correlation analytic design with a cross-sectional approach. The research design used a quantitative plan. This research was conducted at dr. Suhatman Hospital MARS in Dumai City. Sampling technique using Purposive Sampling. There is a relationship between medication adherence and quality of life of asthma patients at dr. Suhatman MARS Hospital with a p-value of 0.000 and a correlation coefficient of 0.621. Adherence to medication use has a relationship with the quality of life of asthma patients at RSUD dr. Suhatman MARS Dumai City.